2022
DOI: 10.3389/fnut.2022.827093
|View full text |Cite
|
Sign up to set email alerts
|

A County-Level Spatial Study of Serum Selenoprotein P and Keshan Disease

Abstract: BackgroundKeshan disease (KD) is strongly associated with selenium deficiency. Selenoprotein P (SELENOP) is a recognized molecular biomarker of selenoproteins and an important indicator of selenium nutrition. This study was aimed at providing geographically precisely visualized evidence of selenium nutrition at molecular level for assessing KD prevention, control, and elimination on the etiological perspective.MethodsWe used spatial ecological design for this study. The serum SELENOP levels of the residents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Recently, a large and wide scope study, including a total of 6,382 individuals recruited from 1,688 counties in 29 provinces in mainland China, was conducted to explore the role of serum Se and SEEP1 levels in KD. The results showed that Se deficiency may still exist among residents living in some KD-endemic areas, who are still at risk of KD, suggesting the need for a diet rich in Se for the residents in KD-endemic areas [ 53 ]. However, the mean serum SEPP1 levels of the residents living in the KD-endemic counties were not significantly lower than those of the residents living in the KD nonendemic counties, which indicated that SEPP1 may not properly reflect the Se status [ 53 ].…”
Section: Se Deficiency and Keshan Disease (Kd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a large and wide scope study, including a total of 6,382 individuals recruited from 1,688 counties in 29 provinces in mainland China, was conducted to explore the role of serum Se and SEEP1 levels in KD. The results showed that Se deficiency may still exist among residents living in some KD-endemic areas, who are still at risk of KD, suggesting the need for a diet rich in Se for the residents in KD-endemic areas [ 53 ]. However, the mean serum SEPP1 levels of the residents living in the KD-endemic counties were not significantly lower than those of the residents living in the KD nonendemic counties, which indicated that SEPP1 may not properly reflect the Se status [ 53 ].…”
Section: Se Deficiency and Keshan Disease (Kd)mentioning
confidence: 99%
“…The results showed that Se deficiency may still exist among residents living in some KD-endemic areas, who are still at risk of KD, suggesting the need for a diet rich in Se for the residents in KD-endemic areas [ 53 ]. However, the mean serum SEPP1 levels of the residents living in the KD-endemic counties were not significantly lower than those of the residents living in the KD nonendemic counties, which indicated that SEPP1 may not properly reflect the Se status [ 53 ]. However, the serum SEPP1 levels in 2,351 subjects living in rural areas, general cities, and developed cities in 15 KD-endemic provinces and 13 KD nonendemic provinces in China were measured [ 54 ].…”
Section: Se Deficiency and Keshan Disease (Kd)mentioning
confidence: 99%
“…Selenium is among the essential trace elements for mammals and mainly performs its biological functions as selenocysteine to synthesize selenoprotein (Schomburg et al 2004 ). In the past century, selenium deficiency was discovered to be the main reason for endemic diseases, such as Keshan disease and Kashin–Beck disease (Jia et al 2022 ; Wang et al 2020 ). Selenocysteine (Sec) is the 21st amino acid encoded by TGA, which was discovered in 1986 and plays a crucial role in the active center of some antioxidant enzymes, including the glutathione peroxidase (GSH-Px) family and thioredoxin reductase (TrxR).…”
Section: Introductionmentioning
confidence: 99%
“…Keshan disease occurs when vascular endothelial cells are damaged from oxidative stress due to non-functional antioxidant proteins ( 8 ). This disease also causes some serious health problems such as atherosclerosis, hypertension, myocardial necrosis and congestive heart failure ( 9 ). Kashin-Beck disease is an endemic osteoarthropathy, causing severe symptoms to joints and bone, including joint pain, elbows flexion and extension disturbances, enlarged inter-phalangeal joints, and limited joint motion ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%